2018
DOI: 10.1155/2018/1361402
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolomic Study of Chlorogenic Acid in a Rat Model of Chronic Sleep Deprivation Using Gas Chromatography-Mass Spectrometry

Abstract: The urinary metabolomic study based on gas chromatography-mass spectrometry (GC-MS) had been developed to investigate the possible antidepressant mechanism of chlorogenic acid (CGA) in a rat model of sleep deprivation (SD). According to pattern recognition analysis, there was a clear separation among big platform group (BP), sleep deprivation group (SD), and the CGA (model + CGA), and CGA group was much closer to the BP group by showing a tendency of recovering towards BP group. Thirty-six significantly change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Recent studies have shown that chlorogenic acid has a significant improvement effect in rat models of sleep deprivation, and the mechanism might regulate the abnormal pathways of arginine and proline metabolism. 41 At the same time, we found that proline was the only disturbed metabolite in this pathway, and its up-regulation might relate the decline of the metabolic levels. According to a previous study, cysteine and methionine is likely associated with psychiatric condition.…”
Section: Discussionmentioning
confidence: 75%
“…Recent studies have shown that chlorogenic acid has a significant improvement effect in rat models of sleep deprivation, and the mechanism might regulate the abnormal pathways of arginine and proline metabolism. 41 At the same time, we found that proline was the only disturbed metabolite in this pathway, and its up-regulation might relate the decline of the metabolic levels. According to a previous study, cysteine and methionine is likely associated with psychiatric condition.…”
Section: Discussionmentioning
confidence: 75%
“…Urine metabolites were performed following an untargeted gas chromatography-time-of-flight mass spectrometer (GC-MS) metabolomics method, as described previously ( Ma et al, 2018 ). In brief, urinary samples were first thawed at room temperature, shaken well, and then centrifuged at 12,000 rpm for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The urinary metabolomics study was based on an untarget GC–MS metabolomics method according to our previously published methods with minor modifications [ 45 ]. Briefly, 2.0 mL sample was centrifuged at 12,000 rpm for 10 min after thawing the mouse urine sample at room temperature.…”
Section: Methodsmentioning
confidence: 99%